Kinerja Organisasi Kemahasiswaan Hubungannya dengan Terminologi Human Capital - Setyowulan, Dese; Lia, Nadia Tri Asfa; Azizah, Rafidah; Sunandar, Asep; Adha, Maulana Amirul (J-MPI (Jurnal Manajemen Pendidikan Islam), 2020)
This study aims to determine, 1) the level of human capital of student organizations, (2) the level of student organization performance, (3) the relationship of human capital to the performance of student organizations in the Faculty of Education (FIP) Malang State University (UM). This research uses a quantitative approach with a descriptive correlational research design. The research instrument used was a questionnaire with respondent members of student organizations in FIP UM. The analysis technique used in this research is descriptive analysis and correlation. The results of this study indicate: (1) the level of human capital of student organizations in the Faculty of Education UM is quite good; (2) the level of performance of student organizations in the Faculty of Education UM is quite good and (3) there is a positive and significant relationship between human capital on the performance of student organizations in the Faculty of Education, State University of Malang.